Pemberdayaan Ekonomi Umat Dalam Perspektif Islam (Sebuah Upaya dan Strategi) - Dian Iskandar Jaelani (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
Islam has taught its followers to try to get a good life in this world and in the hereafter in order to achieve well-being both physically and spiritually. Therefore no exaggeration to Islam as a religion can also be said of empowerment, which seeks to empower believers to live a well-balanced between the needs of the duniawi and ukhrawi. So far the Indonesian Islamic community, especially as the majority of people, is still too far away from all the advantages when compared with people in other countries, especially countries which are some of the western Christian, especially the economy. Even very unfortunate, in Islamic societies has occurred which led to economic inequality of wealth circulation only rotates in a group of bourgeois alone. This fact calls for economic empowerment efforts are systematic and continuous to deliver economically egalitarian society and circulation of wealth can be enjoyed by society equally. Therefore, the necessary breakthroughs or empowerment methods that hit. This paper will explain how the efforts and strategies of community economic empowerment in the Islamic perspective.